ISSUES AND PROSPECTS FOR THE DEVELOPMENT OF HUNGARIAN AGRICULTURE AT THE TURN OF THE XIX-TH AND XX-TH CENTURIES IN DISPATCHES OF RUSSIAN DIPLOMATS - Kryuchkov, Igor Vladimirovich (Közép-Európai Közlemények, 2020)
The attitude of Russian diplomats working in Hungary (Budapest, Fiume (Rijeka) towards issues and prospects for the development of agriculture of the country at the turn of the 19th and 20th centuries in conditions of the world agricultural crisis of the last third of the 19th century is considered in the article. In general, they appreciated agricultural policy of the Hungarian government directed at modernizing agriculture of the country that, however, did not stop diplomats from criticizing it for insufficient speed in taking decisions in conditions of crisis situations. Achievements of Hungary in the field of modernization of agriculture and increase of its export potential were perceived as useful experience in forming its own agricultural policy in Russia.